The Influence of Digital Literacy of Teachers on the Implementation of Online Learning at High Schools in Gowa Regency - Dharma, Surya; Ansyarif, Azmalaeni Rifkah (IJER (Indonesian Journal of Educational Research), 2023)
In connection with the efforts to improve the quality of education in the 21st century, teachers are demanded for their professionalism and are obliged to develop academic qualifications and competences in a sustainable manner in line with the development of science, technology, and arts. The use of digital information technology in the learning process first requires teachers to speak against all information technology and digital developments. This is necessary to support the education system as well as the development of digital learning resources so that students can access them using technology. Based on this, research was carried out aimed at finding out the influence of digital literacy among teachers on the implementation of online learning. This research is being carried out throughout the state high schools in Gowa Regency. The population in this study is a total of 238 civil service teachers spread across five schools. Sampling was done using the random proportional sampling technique with samples of 70 teachers based on the Slovin formula. The data collection technique uses a questionnaire that tests the validity of the contents using the gregory test model and the validation of the construction using the confirmatory factor analysis technique, and the rehabilitation test using the Cronbach alpha formula, which produces a reliability coefficient value of 0.98 for the teacher's digital literacy instrument and a reliability coefficient of 0.96 for the online learning implementation instrument. The simple linear regression technique is used to analyze the data obtained. The results of the study revealed that there is a positive and significant influence of the digital literacy of teachers on the implementation of online learning at the State High School Preventing Education in Gowa Regency, and the great contribution or impact of the digital literature of the teacher on online learning implementation is 48%. There are findings in this study that reveal that there is a positive and significant influence of digital literacy teachers on the implementation of online learning. This shows that the quality of learning online is determined by the professionalism of teachers in the aspect of the ability to use digital technology.